PENGGUNAAN EMOTIONAL FREEDOM TECHNIQUE (EFT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA - CECE HERMAWAN (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2022)
The purpose of this study was to determine the application of the Emotional Freedom Technique model to improve student learning outcomes in class VIII Mts. Darul Ulum YTM Tanjung Sari, Bogor Regency. and knowing the obstacles experienced by students regarding learning outcomes on prism and pyramid material. The method used in this study is a quasi-experimental method and data collection techniques with tests, questionnaires, and observations. The population in this study were students of class VIII Mts. Darul Ulum YTM Tanjung Sari, Bogor Regency. The sampling technique used was Cluster Random Sampling. The first hypothesis, the application of the Emotional Freedom Technique model can improve student learning outcomes in class VIII MTs. Darul Ulum YTM Tanjung Sari, Bogor Regency, was verified by looking at the results of the pretest and posttest. The average value of the initial test (pretest) in the EFT method class is 18,333 with an ability level of 18% which indicates a low level, while the average value of the final test (posttest) is 34,667 with an ability level of 34% which indicates a low level, in other words experienced an increase of 15% or 55. Based on these data, it can be seen that there was an increase in the learning process of students after using the Emotional Freedom Technique model. This shows a significant increase. Thus, the Emotional Freedom Technique model can improve student learning outcomes even though students experience obstacles. ABSTRAKTujuan penelitian ini untuk mengetahui penerapan model Emotional Freedom Technique untuk meningkatkan hasil belajar siswa pada siswa kelas VIII Mts. Darul Ulum YTM Tanjung Sari Kabupaten Bogor.dan mengetahui kendala yang dialami siswa mengenai hasil belajar pada materi prisma dan limas. Metode yang digunakan dalam penelitian ini adalah metode quasi eksperimen dan teknik pengumpulan data dengan tes, angket, dan observasi. Populasi dalam penelitian ini siswa kelas VIII Mts. Darul Ulum YTM Tanjung Sari Kabupaten Bogor. Teknik pengambilan sampel dengan menggunakan Cluster Random Sampling. Hipotesis pertama, penerapan model Emotional Freedom Technique dapat meningkatkan hasil belajar siswa pada kelas VIII MTs. Darul Ulum YTM Tanjung Sari Kabupaten Bogor teruji kebenarannya dengan melihat hasil pretest dan posttest. Nilai rata-rata tes awal (pretest) di kelas metode EFT yaitu 18.333 dengan tingkat kemampuan 18% yang menunjukan taraf rendah, sedangkan nilai rata-rata tes akhir (posttest) yaitu 34.667 dengan tingkat kemampuan 34% yang menunjukan taraf kurang, dengan kata lain mengalami peningkatan 15% atau 55. Berdasarkan data tersebut dapat diketahui terjadi peningkatan dalam proses pembelajaran pada siswa setelah menggunakan model Emotional Freedom Technique. Hal tersebut menunjukan adanya peningkatan yang signifikan. Dengan demikian, model Emotional Freedom Technique dapat meningkatkan hasil belajar siswa meskipun siswa mengalami kendala.